Evaluasi Sistem Pengelolaan Sampah Di Perumahan Telaga Murni RW 016 - Erwin Fraditya; Mayang Sari Juita; Nur Ilman Ilyas (Prosiding Sains dan Teknologi, 2022)
All those who are active will definitely produce waste and the same thing happened in Telaga Murni Housing RW 016, Cikarang Barat District, Bekasi Regency. The purpose of this study was to determine and create a waste management planning system in Telaga Murni Housing RW 016, Cikarang Barat District, Bekasi Regency. The research method used is a literature study method in the form of collecting information from literature such as lecture materials, research references, and also from documentation regarding the field conditions of RW 016, West Cikarang District, Bekasi Regency so that a design can be made that can be used as an alternative solution for the management planning system. waste in the area. Keywords: Environment, Garbage, Data, Evaluation